The Impact of Cartoons on Children's Behavior - Khalikul Bahri; Yusri; Syahril Furqany (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2019)
The phenomena of behavioral changes that have occurred in children aged (6-12 years) in recent years have been influenced by movie shows, especially cartoon films. This study aims to determine the impact of cartoon films on children's behavior. In addition, it is also to find out what are the negative effects of cartoon movies on children in Gampong Seukeum Bambong Delima District, Pidie Regency. This research uses a qualitative approach by analyzing descriptive data analysis. The type of research is field research, using direct observation, interviews and documentation. The results showed that the impact of cartoon films on children in Gampong Seukeum Bambong, Delima District, Pidie Regency is very influential on children's behavior such as asking parents to buy Boboiboy clothes and new bicycles, fighting with their friends and with their own siblings, often doing bicycle jumping scenes, reckless in playing bicycles. The positive impact of cartoon movies for children such as increasing children's creativity, fostering children's social values and improving children in Indonesian. While the negative impact of cartoon films on children is to make them inattentive, lazy to learn / forget learning time, aggressive behavior, impolite speech, too high imagination, lack of focus, health problems (visual impairment) and irregular emotions. Steps to prevent behavioral changes in children control all children's activities outside the home, regulate television viewing hours and guide children towards positive things so as not to fall into negative things.